Yolonda's Genius - Carol Fenner (Aladdin, 1997)
Yolanda is smart, tough, and big for her age. Back in Chicago where they used to live, everyone knew better than to mess with her or her little brother, Andrew. Andrew doesn$1 (Bt talk very much and he can$1 (Bt read, but he can create unbelievable music on the old harmonica their father left him. When Yolanda reads the definition of (3z(Bgenius(3y (Bin the dictionary, she knows it describes Andrew, and she$1 (Bs determined to convince the world, especially their mother, of Andrew$1 (Bs gift. Then one day when Yolanda$1 (Bs back is turned, the unthinkable happens, and the music stops. Now Yolanda$1 (Bs mission is more important than ever. How can she open people$1 (Bs eyes to Andrew$1 (Bs talent and help him find the music again?s
Keywords: Historical Fiction -- Historical Fiction